Antinociceptive and Anti-Inflammatory Activities of Teucrium persicum Boiss. Extract in Mice. (16th November 2015) - Miri, Abdolhossein; Sharifi-Rad, Javad; Tabrizian, Kaveh; Nasiri, Ali Akbar
Abstract : Background. Therapeutic properties of Teucrium species as antioxidant, antibacterial, analgesic, anticancer, diuretic, and tonic compounds have been proved earlier. Materials and Methods . In this study, the antinociceptive and anti-inflammatory effects of the aqueous extract of Teucrium persicum on chronic pain, sciatic nerve ligation as a model of neuropathic pain, and inflammatory models were investigated by formalin, hot-plate, and cotton pellet-induced granuloma models in mice, respectively. T. persicum aqueous extracts (100, 200, and 400 mg/kg) were orally gavaged for one week. On 8th day, the time spent and the number of lickings were recorded in formalin test. Morphine and Diclofenac were used intraperitoneally as positive controls. In sciatic nerve ligated animals, as a model of neuropathic pain, doses (100, 200, and 400 mg/kg) of T. persicum extract (TPE) were orally gavaged for 14 consecutive days. The analgesic effect of this extract was examined 14 days after sciatic nerve ligation using the hot-plate test. Controls received saline and Imipramine (40 mg/kg, i.p.) was used a positive control for neuropathic pain model. Results. In the formalin test, a week oral gavage of all TPE doses (100, 200, and 400 mg/kg) caused a significant decrease on the licking response compared to the control negative animals. In the hot-plate test, doses of 200 and 400 mg/kg showed significant analgesic effects in sciatic nerve ligated animals. Oral gavaged of TPE revealed significant analgesic effect on chronic pain in both formalin test and sciatic nerve ligated animals. The TPEs did not have any significant anti-inflammatory effects in cotton pellet-induced granuloma formation in mice. Conclusions. These results suggest that the aqueous extract from T. persicum Boiss. produced antinociceptive effects. Its exact mechanism of action still remains indistinct.